Optimization of Polypropylene-Modified Asphalt Mixtures for Enhanced Road Durability in Tropical Regions: Advancing Sustainable Infrastructure Development Aligned with SDG 9 and SDG 12 - Ahmad Rafii; Sani Isah; Adam Balcerzak; Rashidah Mohammad Ibrahim; Bincar Nasution (AMPLITUDO : Journal of Science and Technology Innovation, 2026)
Road pavements in tropical regions experience accelerated deterioration due to high temperatures; intense rainfall; and high humidity; necessitating innovative solutions that address both infrastructure durability and environmental sustainability. This experimental study evaluates asphalt mixtures modified with polypropylene (PP) plastic waste to enhance performance under tropical climate conditions. Laboratory samples containing 0% (control); 4%; 6%; and 8% PP by binder weight were subjected to Marshall stability; penetration; accelerated aging (Rolling Thin Film Oven Test and ultraviolet radiation); and moisture susceptibility testing. Results demonstrate that 6% PP incorporation yielded optimal performance; with Marshall stability increasing to 14.5 kN (22% improvement over control); penetration decreasing to 58 dmm (18% reduction); and post-aging stability retention of 85%. Moisture conditioning tests revealed reduced stability loss at 13.8% compared to 24.4% for control mixtures; indicating enhanced moisture resistance. Economic analysis confirms cost savings of approximately 30% when substituting recycled PP waste for conventional polymer modifiers such as SBS. These findings identify 6% PP as the optimal dosage for tropical asphalt applications; demonstrating the technical and economic feasibility of circular material approaches in infrastructure engineering.